PENGELOLAAN KEUANGAN RUMAH TANGGA DI ERA COVID-19 BERBASIS EKONOMI ISLAM PADA JAMAAH PEREMPUAN MASJID AL-MUTTAQIN DUSUN KALIREJO DESA NGUNGGAHAN KECAMATAN BANDUNG KABUPATEN TULUNGAGUNG - adlan, Aqim (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
This study aims to actualize the management of household finances based on Islamic economics in female congregations of the Al-Muttaqin Mosque. This is because in the Covid-19 pandemic situation, the family is one of the components affected by economic stability. Thus, through the model of empowering family financial management based on Islamic economics for the female congregation of the Al-Muttaqin mosque, it is very important. Through very in-depth mentoring and study, this work resulted in the finding that in the era of the Covid-19 pandemic, the management of household finances based on Islamic economics for the female congregation of the Al-Muttaqin mosque is very important because the situation and economic downturn have an impact on household finances. So that the management of household finances based on Islamic economics becomes a solution.